2022
DOI: 10.1038/s41409-022-01755-x
|View full text |Cite
|
Sign up to set email alerts
|

Late endocrine effects after hematopoietic stem cell transplantation in children with nonmalignant diseases

Abstract: The number of children undergoing hematopoietic stem cell transplantation (HSCT) for nonmalignant diseases has increased in recent years. Endocrine complications are common after HSCT for malignant diseases, while little is known about long-term prevalence and risk factors in children transplanted for nonmalignant diseases. We retrospectively evaluated gonadal function, near adult height and thyroid function in 197 survivors of pediatric HSCT for hemoglobinopathies (n = 66), inborn errors of immunity/ metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…However, those study populations differed considerably in their demographic characteristics, underlying diseases, method of HSCT, preconditioning regimens, and presence or severity of GVHD. The overall prevalence of late endocrine effects from HSCT in those studies ranged from 35.7% to 65.2% [ 8 , 9 , 12 ]. Our group previously reported that endocrine complications occurred in 30% of children with noncentral nervous system solid tumors; among them, 63.3% had undergone HSCT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those study populations differed considerably in their demographic characteristics, underlying diseases, method of HSCT, preconditioning regimens, and presence or severity of GVHD. The overall prevalence of late endocrine effects from HSCT in those studies ranged from 35.7% to 65.2% [ 8 , 9 , 12 ]. Our group previously reported that endocrine complications occurred in 30% of children with noncentral nervous system solid tumors; among them, 63.3% had undergone HSCT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although demographic factors, chemotherapy, radiation, GVHD, and glucocorticoid use all affect the development of endocrine complications, previous studies reported that the age at HSCT significantly influences clinical outcomes and chronic health issues in childhood cancer survivors [ 8 , 9 ]. Several comparative studies have assessed endocrine outcomes in childhood cancer survivors according to age or pubertal stage at HSCT [ 10 - 12 ]. They reported that age at HSCT affects growth and gonadal function.…”
Section: Introductionmentioning
confidence: 99%
“…The potentially lower occurrence of endocrine late effects following treosulfan versus busulfan has been extensively investigated in the last decade, but with a specific focus on gonadal function ( 57 ). Only recently, two retrospective studies have highlighted that treosulfan seems to show a trend towards a safer toxicity profile on thyroid health, though longer-lasting additional analyses are warranted before this conclusion can be systematically drawn ( 18 , 58 ).…”
Section: Thyroid Dysfunction and Autoimmune Disordersmentioning
confidence: 99%
“…7,8 Due to the HSCT procedure, consisting of chemotherapy and immunosuppressants, or due to the underlying disease, potential late effects can arise, such as gonadal dysfunction, renal insufficiency and cognitive problems, which consequently impair health-related quality of life. [9][10][11][12][13][14] Proper screening for these late effects requires a dedicated long-term follow-up programme, which has been implemented at the Leiden University Medical Center (LUMC) in the Netherlands, providing comprehensive care from 2 years after HSCT onwards. 9,10 The programme includes annual monitoring of both physical and mental health (Supporting Information S1: Figure 1), and continues throughout adulthood due to the potential for late effects to occur even many years after paediatric HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…HSCT has proven to be an intensive, curative treatment option for various severe paediatric diseases, including nonmalignant disorders such as inborn errors of immunity, hemoglobinopathies and bone marrow failure syndromes 7,8 . Due to the HSCT procedure, consisting of chemotherapy and immunosuppressants, or due to the underlying disease, potential late effects can arise, such as gonadal dysfunction, renal insufficiency and cognitive problems, which consequently impair health‐related quality of life 9–14 . Proper screening for these late effects requires a dedicated long‐term follow‐up programme, which has been implemented at the Leiden University Medical Center (LUMC) in the Netherlands, providing comprehensive care from 2 years after HSCT onwards 9,10 .…”
Section: Introductionmentioning
confidence: 99%